Use of rubberized engineered cementitious composite in strengthening flexural concrete beams. (1st July 2022) - AbdelAleem, Basem H.; Hassan, Assem A.A.
Highlights: Flexural performance of composite beams strengthened with rubberized ECC was investigated. Different types of rubber aggregate were investigated. Strengthening concrete beams at different cross-sectional location was investigated. Placing rubberized ECC in compression side enhanced the ductility and energy absorption. Using powder rubber in strengthening layer exhibited better structural performance compared to crumb rubber. Abstract: This study aimed to investigate the flexural behavior of reinforced concrete beams strengthened with high-performance rubberized engineered cementitious composite (RECC) at different cross-sectional positions (compression and tension zones). The RECC material was developed with different sizes of rubber particles, including 4.75 mm crumb rubber (CR) and 0.4 mm powder rubber (PR). The investigation tested conventional normal concrete (NC) and two full RECC beams with CR and PR as reference beams for comparison. A four-point bending test was conducted to evaluate the flexural strength, ductility, energy absorption, deformability, first cracking load, and cracking behavior of the strengthened beams compared to the reference beams. The study also compared the experimental results and their theoretical predictions calculated by design code equations and proposed model from the literature. The results revealed that using a RECC layer in the compression side exhibited a significantly higher deformability, cracking behavior, ductility, and energy absorption compared to the reference NC beam. Meanwhile, placing a RECC layer in the tension side showed lower ductility and energy absorption capacity compared to counterpart beams strengthened in the compression side, but still higher than the NC reference beam. The results also indicated that strengthening the beam in the compression side with a RECC layer developed with PR showed better enhancement in the energy absorption and ductility compared to a RECC layer developed with CR.